Men of war - O'Brian, Patrick 1914-2000 (Norton, 1995)
This richly illustrated book offers a concise overview of the historical background to Patrick O'Brian's acclaimed Aubrey/Maturin series, a straightforward exploration of what daily life in Nelson's navy was really like for everyone from the captain to the rawest recruit. Line drawings and charts help us to understand the construction and rigging of the great ships, the types and disposition of the guns, and how they were operated in battle. Contemporary drawings and cartoons illustrate aspects of naval life from the press gang to the scullery. Finally, a generous selection of full-color paintings renders the majesty and the excitement of fleet actions in the age of fighting sail.
Keywords: Geschichte 1700-1800; Geschichte 1800-1900; Geschichte; Seafaring life -- History -- 18th century; Ships of the line -- History -- 18th century; Seeschifffahrt; Kriegsschiff